(488) the fourth long-term training program البرنامج التدريبي الرابع طويل الأمد (the institute of national planning, 2018)
This academic document presents the structure and content of the Fourth Long-Term Training Program developed by the Institute of National Planning as an integrated educational framework designed to prepare specialized personnel in economic planning, social development, and quantitative analysis. The document argues that qualified human resources constitute a fundamental requirement for successful development planning; consequently, the program was designed to combine theoretical instruction, practical training, and research activities within a comprehensive educational structure. The program includes a set of core courses covering general planning, national accounting, economic development, economics of economic systems, general and advanced economic theory, econometrics, and planning methods. The distribution of instructional hours reflects an emphasis on integrating theoretical knowledge with practical applications. The curriculum seeks to provide trainees with analytical and methodological foundations necessary for understanding complex economic relationships and applying them to practical planning situations. The document also emphasizes the importance of research training as a major component of the program. Each participant is required to conduct a supervised research project under the guidance of faculty members. This research component serves as a mechanism for strengthening independent analytical capabilities, scientific research skills, and competence in dealing with economic data and planning models. Furthermore, the document addresses selected problems in economic planning, including national accounting systems, input-output tables, and physical balance techniques, which are presented as important analytical tools for understanding economic structures, examining sectoral interrelationships, and estimating future development requirements. Advanced seminars are also included to promote scholarly discussion and deeper understanding among researchers and trainees. The document concludes that preparing professional planners depends not only on delivering theoretical knowledge but also on developing advanced analytical and research capabilities capable of supporting effective development planning and evidence-based economic decision-making.